Comparision of heavy metals removal from comtaminated soil by siam weed (Chromolaena odorata) and vetiver grass (Vetiveria zizanioides) - Wilaiwan Chaengcharoen (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007